2013
DOI: 10.1521/pedi_2013_27_111
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental Trajectories to Male Borderline Personality Disorder

Abstract: Due to the higher diagnostic prevalence of borderline personality disorder (BPD) in females, there exists a dearth of literature on the manifestations of BPD in men and minimal information on male developmental trajectories to the disorder. To identify precursors of BPD in males, surveys were administered to parents about their BPD male offspring and non-BPD male siblings. Questions covered aspects of probands' lives from infancy to late adolescence. BPD offspring were identified through self-reported clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
(46 reference statements)
1
11
0
1
Order By: Relevance
“…A recent study by Laporte and colleagues also underlined the important role of temperamental traits in the development of BPD, those traits being the main difference between BPD probands and their sisters free of psychopathology, who both reported similar relationships with their parents. Likewise, studies focusing on the perspective of parents of BPD probands reported that both a child's difficult temperament (i.e., unusual sensitivity, moodiness) and a conflictual PCR were significant predictors of BPD diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Laporte and colleagues also underlined the important role of temperamental traits in the development of BPD, those traits being the main difference between BPD probands and their sisters free of psychopathology, who both reported similar relationships with their parents. Likewise, studies focusing on the perspective of parents of BPD probands reported that both a child's difficult temperament (i.e., unusual sensitivity, moodiness) and a conflictual PCR were significant predictors of BPD diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two studies measured parental perspective on BPD child's behaviour compared to their non‐BPD siblings. The 2010 study asked parents to compare their BPD daughter to their other non‐BPD daughters, while the 2013 study compared BPD sons to their non‐BPD brothers.…”
Section: Perspective Of Parents Of Borderline Personality Disorder Prmentioning
confidence: 99%
“…To this end, recent personality disorder research has focused on developmental issues with relevance for multiple personality disorder constructs, including reward processing (White et al, 2014), stress responses , emotion regulation (Gratz et al, 2014) and social cognition (Sharp & Vanwoerden, 2014). Over recent years there has been increasing interest in the emergence of borderline personality disorder (Arens et al, 2013;Bornovalova, Hicks, Iacono, & McGue, 2013;Chanen & McCutcheon, 2013;Stepp, Olino, Klein, Seeley, & Lewinsohn, 2013) and evidence to suggest that the disorder may have roots in early development is accumulating (Goodman, Patel, Oakes, Matho, & Triebwasser, 2013;Lopez-Castroman et al, 2013;Perroud et al, 2013;Siever, 2008). In this paper, building on earlier work on the significance of attachment and mentalization for the development of BPD (see Allen, Fonagy, & Bateman, 2008;Fonagy & Luyten, 2009;Fonagy & Luyten, in press;Fonagy, Luyten, & Strathearn, 2011), we propose a developmental framework that conceptualizes BPD in terms of a specific underlying vulnerability to psychopathology (Fonagy, Luyten, & Allison, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Life-time prevalence of BPD is estimated between 0.7% and 2.3% in males [ 1 , 2 ]. While studies of community samples generally report no sex differences in the prevalence of BPD [ 3 5 ], fewer males than females seek treatment for BPD [ 6 8 ]. Consequently, little is known about men with BPD.…”
Section: Introductionmentioning
confidence: 99%